STRATEGI GURU MENGATASI PERILAKU DISRUPTIF SISWA DALAM PEMBELAJARAN DI SEKOLAH DASAR - Khotimah, Nur (Badan Perencanaan Pembangunan Daerah dan Penelitian dan Pengembangan Kabupaten Wonogiri, 2024)
This research is motivated by the number of students who do disruptive activities duringin the classroom. The purpose of this study is to describe in detaildetail teachers' strategies regarding disruptive behavior in elementary school students. The method in this research is a single phenomenology or case study. The place of research was conducted at SD NegeriWidoro, Wonogiri Regency with 36 students as participant.The data collection techniques used in the research were observation and interviews. Instruments for data collection use observation and interview sheets which have been validated by experts. The data analysis techniques used include data reduction, data display, and data verification. The results showed that the contributing factors were the lack of motivation from the teacher, the teacher being negative towards students, inconsistent parenting patterns, lack of parental care for children, overprotective parents, and poor teaching quality. The teacher's strategy in overcoming disruptive behavior uses three approaches, namely behavioristic, cognitive, and humanistic.Students' preferences in dealing with disruptive behavior lie in the problem of learning styles that must be adapted to the way teachers teach their students.